The effect of multiple exposures in scenario‐based simulation-A mixed study systematic review - Alette H. Svellingen; Margrethe B. Søvik; Kari Røykenes; Guttorm Brattebø (Wiley, 2021)
Abstract Aims To examine the use and effects of multiple simulations in nursing education. Design A mixed study systematic review. Databases (CINAHL, Medline, PubMed, EMBASE, ERIC, Education source and Science Direct) were searched for studies published until April 2020. Method Researchers analysed the articles. Bias risk was evaluated using the Critical Appraisal Skills Programme and Cochrane Risk of Bias tool. Results In total, 27 studies were included and four themes identified. Students participated in multiple simulation sessions, over weeks to years, which included 1-4 scenarios in various nursing contexts. Simulations were used to prepare for, or partly replace, students' clinical practice. Learning was described in terms of knowledge, competence and confidence. Conclusion Multiple scenario‐based simulation is a positive intervention that can be implemented in various courses during every academic year to promote nursing students' learning. Further longitudinal research is required, including randomized studies, with transparency regarding study design and instruments.